2006
DOI: 10.3164/jcbn.38.45
|View full text |Cite
|
Sign up to set email alerts
|

Study of Taste Changes for Salt and Restriction of Salt in Preeclampsia

Abstract: Summary We studied the salt taste change during pregnancy and investigated its meaning in normal pregnancy and preeclampsia female in salt restriction. 40 normal pregnant female, 35 pregnant female with preeclampsia and 64 healthy non-pregnant female were recruited to this study. Gustatory test was performed with the filter-paper disk method. Salt solutions, 0.1, 0.2, 0.4, 0.6, 0.8 and 1.0 weight % were made from reagent grade sodium chloride and distilled water. The threshold of salt taste in pregnant female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…23 A change in taste sensitivity has been reported in similar studies on pregnant women. 6,7,24,25 The taste detection threshold of pregnant women was significantly lower when compared to nonpregnant women (P ¼ .002 or Table 2). Decrease in a particular taste sensitivity or detection threshold will make the individuals to add supplements that will improve the missing taste to their food so as to have savory meals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…23 A change in taste sensitivity has been reported in similar studies on pregnant women. 6,7,24,25 The taste detection threshold of pregnant women was significantly lower when compared to nonpregnant women (P ¼ .002 or Table 2). Decrease in a particular taste sensitivity or detection threshold will make the individuals to add supplements that will improve the missing taste to their food so as to have savory meals.…”
Section: Discussionmentioning
confidence: 97%
“…31 An increased sensitivity to bitter taste would increase the risk of hyperemesis which can be harmful to both mother and fetus. 32 The decrease in gustatory function in pregnancy had been explained by the need for increased intake of salt and calories, 8,24 changes in serum concentration of trace elements, 22,28 and changes in serum estrogen and progesterone levels. 7,28,33,34 Experimental studies on rat have demonstrated estrogen receptors in brain areas involved in gustatory processing, 35 and estrogen is known to affect gene expression within the central nervous system.…”
Section: Discussionmentioning
confidence: 99%